Search for new resonances in mass distributions of jet pairs using 139 fb −1 of pp collisions at √s = 13TeV with the ATLAS detector - Fiolhais, M. C. N. (2020)
A search for new resonances decaying into a pair of jets is reported using the dataset of proton-proton collisions recorded at p s = 13TeV with the ATLAS detector at the Large Hadron Collider between 2015 and 2018, corresponding to an integrated luminosity of 139 fb1. The distribution of the invariant mass of the two leading jets is examined for local excesses above a data-derived estimate of the Standard Model background. In addition to an inclusive dijet search, events with jets identi ed as containing b-hadrons are examined speci cally. No signi cant excess of events above the smoothly falling background spectra is observed. The results are used to set cross-section upper limits at 95% con dence level on a range of new physics scenarios. Model-independent limits on Gaussian-shaped signals are also reported. The analysis looking at jets containing b-hadrons bene ts from improvements in the jet avour identi cation at high transverse momentum, which increases its sensitivity relative to the previous analysis beyond that expected from the higher integrated luminosity.